The fund industry how your money is managed - Pozen, Robert C. (Wiley finance series, 2011)
Details how mutual funds are marketed, regulated, and invested in stocks and bonds. The book also describes the critical factors needed to choose a specific fund for your investment or retirement plan, including what to look for when reading prospectuses, shareholder reports and third party reviews. In addition, the book: Discusses the spread of mutual funds to Asia, Europe, and Latin America -- Compares mutual funds to other investment vehicles such as hedge funds and ETFs -- Shows how to sort mutual funds by categories and subcategories based on security type and investment objective